2022
DOI: 10.21037/tcr-22-778
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant pericardial mesothelioma with a survival of 2.5 years: a case report

Abstract: Background Primary malignant pericardial mesothelioma (PMPM) is a highly malignant tumor originating in the pericardium serosum with clinical manifestations presenting as constrictive pericarditis, with pericardial tamponade and heart failure. Malignant pericardial mesothelioma is rare and has a poor prognosis, with an average survival time of 6–10 months. Case Description Herein, we report the case of a 57-year-old female who developed chest tightness and panic for no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The diagnosis of PPM remains challenging, which leads to the situation that the diagnosis is usually made after surgery or at autopsy (2,10,15,18,21). The delayed diagnosis of PPM may be due to its nonspecific syndromes, its similar presentation to benign pericardial diseases, and its non-definitive etiology (1,(6)(7)(8)(10)(11)(12)(13)(14)(15). Our patient also initially had nonspecific symptoms and inconclusive image findings.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The diagnosis of PPM remains challenging, which leads to the situation that the diagnosis is usually made after surgery or at autopsy (2,10,15,18,21). The delayed diagnosis of PPM may be due to its nonspecific syndromes, its similar presentation to benign pericardial diseases, and its non-definitive etiology (1,(6)(7)(8)(10)(11)(12)(13)(14)(15). Our patient also initially had nonspecific symptoms and inconclusive image findings.…”
Section: Discussionmentioning
confidence: 84%
“…It has been suggested that early detection of this disease is the only hope for survival ( 2 ). Unlike pleural mesothelioma, the relationship between PPM and asbestos exposure remains unsettled; some investigators reported an association with asbestos exposure ( 3 , 4 , 16 ), while others reported no or weak correlation ( 6 10 , 12 15 , 17 – 19 ). So far, there is no consensus on the treatment of PPM, although the survival benefit of chemotherapy has been shown to be superior to that of surgery ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, cell wax block diagnosis is the most effective and reliable technique to distinguish benign and malignant effusions. The combination of immunocytochemical staining can help in identifying the primary source, identify the pathological type of the tumor, and further conduct molecular pathological detection, which provides an objective basis for accurate treatment and prognosis of patients and is valuable for extensive clinical promotion ( 8 , 9 ). In summary, localized pericardial thickening and massive pericardial effusions are easily missed and misdiagnosed in patients.…”
Section: Discussionmentioning
confidence: 99%